Problematics of Secular Economic Science Prespective Ismail Raji Al-Faruqi - Jarman Arroisi; Nur Hadi Ihsan; Kusuma Dewi Nur Aini (ITB AAS INDONESIA Surakarta, 2020)
There is no doubt that capitalism is one of the dominant economic systems today, has been transformed into a new ideology. If the beginning only revolved around free markets, unlimited private ownership, then now it is more of a new culture, lifestyle and even civilization. That dictates all aspects of human life. As a civilization, Capitalism has faced resistance from Islam. Islam, which is usually seen as only a religion, is actually more than just a religion, but includes the basic elements of a civilization. If Capitalism builds a civilization with its distinctive points regarding the theory of socio-economic growth, then Islam does not see it as a basic foundation. Today in Islam, the life of the world is always closely related to the concept of the afterlife. Meanwhile, capitalism separates morality from theology. Furthermore, Islam does not deny the need for rationality to solve the problems of world life, but the rational concept in Islam is not only limited to mathematical logic, it also involves a spiritual dimension. By using the descriptive analytical method, this study produces several important conclusions, namely: First, to overcome scientific problems that have been penetrated by secular Western civilization, Second, the development of the ideology of Capitalism has changed the human perspective in thinking resulting in a lack of moral values and secular ideology. Third, the existence of Al-Faruqi's thought which is based on Tawheed which contributes to a solution to the lack of scientific values which also affects the people's mindset. So from the research results it can be concluded that if a science is successful it will destroy all aspects of life both in terms of ideology or morals.